INTUITION AS A COMPONENT OF NON-CLASSICAL RATIONALITY - Hasanova, P.A (LLC (EOOD) "SCIENTIFIC CHRONOGRAPH", 2020)
In philosophical anthropology, reflecting the biological and psychological aspects of human existence, on the one hand, this is the ratio of biological and social, and on the other hand, it is the problem of the connection of the conscious and the unconscious in a person. One of the most pressing problems that we have encountered in scientific and philosophical literature in recent years is the presence of rational and irrational directions in scientific knowledge. Rationality is one of the highest intellectual states, which is inherent in human perception and is an attribute of his thinking. Unconscious actions, which are considered attributes of a person's cognitive activity, are objective processes, such as rational operations based on biosocial laws that affect different areas of the brain, regardless of the consciousness and will of people. However, unlike rational actions, irrational actions generally do not satisfy people, because they are not given in the desired form. However, as in all rational forms, people in their irrational do not remain outside their consciousness, they are attributes of this activity. Human creativity is based on his cognitive abilities, and the essence of his creativity is revealed in cognitive activity. It is no coincidence that the creative components of a person are affected by both his imagination and their perceived images, both in empirical and theoretical knowledge. They function in the human mind in representations of the ideal type for the future.